Gagal Spinal pada Pasien Operasi Amputasi Transfemoral dengan Debridemen dan Penatalaksanaannya - Sudadi; Maryani, Nova; Artika, I Gusti Ngurah Rai (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2017)
A man 64 years old had a traffic accident 12 hours ago, resulting in crush injury on regio left femur and cruris. This man has fasted and for 8 hours and was planned to undergo debridement and transfemoral amputation surgery by orthopedics. The hemodynamic profile of this patient preoperative: stable with HB 8.4, had two colfs of PRC blood transfusion. Vital sign BP 110/55, HR 110x/minute, RR 22x/minute, SpO2 97%. The anesthesia technique planned for the surgery is spinal block anasthesia. Fluid preloading RL 500 ml, intravenous analgesics fentanyl 25 mcq, sitting position, spinal anesthesia L4-L5, CSF (+), blood (-), agent: bupivacaine 0,5 % hyperbaric 15 mg + fentanyl 25 mcq, aspiration (+) barbotage until 4cc. Thus, supine position after spinal anesthesia. Pin Prick result, Sensoric test (-), Motoric Bromage 0, evaluated until 10 minutes, just parasthesia. Pin prick, result sensoric test no sensoric. Block declared failed, conversion to General Anesthesia LMA. Operation held for 2 hours, post-operative patient transfers to High Unit Care.